TREATMENT RESULTS OF PATIENTS WITH VARICOSE VEINS DISEASE FOR TEN YEARS - L. N. Komarova; R. N. Ryakhin; F. S. Aliev; S. A. Zvezda (SINAPS LLC, 2018)
The aim: to study the quality of life of patients with varicose disease of lower extremities, treated for the period from 2007 to 2016 in an operational way, including the RFA method. Materials and methods. We used the following materials in our work: medical histories of the patient of the surgical department, summary data from the department of statistics Departmental Hospital at the station Tyumen JSC «Russian Railways», data of ultrasonic angioscanization of veins of lower extremities. We used the research methods: statistical method, clinical, expert analysis and system approach. The degree of chronic venous insufficiency of lower extremities was determined using the clinical section of the international classification of CEAP (1995). Results and discussion. We analyzed the quality of life of patients with varicose disease of lower extremities after surgical treatment for the period from 2007 to 2016. It was found that the overwhelming majority of patients (83%) had a hereditary factor from the etiologic factors of the disease, obesity in 57% of cases, long-term static loads in 44%, and hormonal contraceptives in 5% of cases. We gave a subjective evaluation of the results of surgical treatment with the classical method (phlebectomy) and the method of radiofrequency obliteration of veins. The average duration of temporary disability of railwaymen after crossectomy and phlebectomy was (18 ± 2,5) days, while after the RFO the majority of patients (70.5%) returned to their usual life on the day of the operation, 23.5% after 2 days after surgery, 8.8% - after 3 days after the operation. It is shown that the promptly conducted operative treatment in a planned manner, without waiting for the development of complications of varicose veins, significantly improves some sections of the patient's quality of life. Conclusion: the process of rehabilitation of patients in the postoperative period is reduced 3 times if surgical intervention with varicose disease of lower extremities is performed by the method of endovenous segmental radiofrequency obliteration of veins.